2020
DOI: 10.1038/s41436-020-0762-0
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in BRCA counseling across providers in a diverse population of young breast cancer survivors

Abstract: Purpose: All women diagnosed with breast cancer (BC) ≤ age 50 should be referred for genetic counseling (GC) and testing. We sought to compare differences in provider practices and access across a racially and ethnically diverse population of young BC survivors. Methods: A registry-based sample of women diagnosed with invasive BC ≤ age 50 from 2009 to 2012 was recruited through the Florida Cancer Registry, and completed a questionnaire and medical record release. Differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…The national shortage of GHPs [ 31 ] coupled with limited access to GHPs in rural areas [ 32 ] and community oncology practices in many states [ 33 ] has resulted in the majority of genetic tests being ordered without the inclusion of a GHP. In fact, we and others have previously reported that the minority of breast cancer patients are tested through a GHP [ 34 , 35 ]. Similar to our findings which showed that only 20% of young breast cancer survivors had genetic testing services provided by a GHP [ 34 ], another study showed that approximately 21% of patients who received genetic testing reported that a genetic counselor ordered their genetic test [ 35 ].…”
Section: Delivery Of Hereditary Breast Cancer Services Across the Care Continuummentioning
confidence: 99%
See 1 more Smart Citation
“…The national shortage of GHPs [ 31 ] coupled with limited access to GHPs in rural areas [ 32 ] and community oncology practices in many states [ 33 ] has resulted in the majority of genetic tests being ordered without the inclusion of a GHP. In fact, we and others have previously reported that the minority of breast cancer patients are tested through a GHP [ 34 , 35 ]. Similar to our findings which showed that only 20% of young breast cancer survivors had genetic testing services provided by a GHP [ 34 ], another study showed that approximately 21% of patients who received genetic testing reported that a genetic counselor ordered their genetic test [ 35 ].…”
Section: Delivery Of Hereditary Breast Cancer Services Across the Care Continuummentioning
confidence: 99%
“…In fact, we and others have previously reported that the minority of breast cancer patients are tested through a GHP [ 34 , 35 ]. Similar to our findings which showed that only 20% of young breast cancer survivors had genetic testing services provided by a GHP [ 34 ], another study showed that approximately 21% of patients who received genetic testing reported that a genetic counselor ordered their genetic test [ 35 ]. Yet there are insurance policies which mandate pre-test genetic counseling be conducted with involvement of a GHP, which may disproportionately reduce genetic testing rates among minority and underserved populations who have decreased access to genetic services [ 36 , 37 ].…”
Section: Delivery Of Hereditary Breast Cancer Services Across the Care Continuummentioning
confidence: 99%
“…Genetic counselling and testing for high-risk, and subsequently moderate-risk, cancer susceptibility genes to guide risk-reduction approaches and clinical management is now commonplace in many HICs. However, access to cancer genetics services is uneven and reflects profound inequities in cancer prevention and control and, more broadly, health disparities 6,[61][62][63][64][65] . For example, McCarthy et al 61 reported a population-based study in two US states, which showed that, among 3,016 women diagnosed with breast cancer in 2007-2009, Black women were 40% less likely to undergo BRCA1/2 testing than white women.…”
Section: Germline Markers Of Risk In the Clinic Multigene Panel Testingmentioning
confidence: 99%
“…[6][7][8][9] Evidence has further shown the utility of molecular profiling in matched therapy outcomes 4,[10][11][12] and the cost efficacy of multigene testing as a precision medicine prevention approach. 13 Recent work highlights the need for equitable access to precision medicine in diverse populations 14 in addition to the growing need to validate the clinical utility and processes behind advances in genetic medicine. [15][16][17] Molecular pathology has become ingrained in cancer diagnostics and therapeutic decision-making.…”
Section: Introductionmentioning
confidence: 99%